Diagnostic accuracy of ultrasound signs for detecting adnexal torsion: systematic review and meta‐analysis. (11th February 2023) - Garde, I.; Paredes, C.; Ventura, L.; Pascual, M. A.; Ajossa, S.; Guerriero, S.; Vara, J.; Linares, M.; Alcázar, J. L.
ABSTRACT: Objective: To evaluate the diagnostic accuracy of different ultrasound signs for diagnosing adnexal torsion, using surgery as the reference standard. Methods: This was a systematic review and meta‐analysis of studies published between January 1990 and November 2021 evaluating ovarian edema, adnexal mass, ovarian Doppler flow findings, the whirlpool sign and pelvic fluid as ultrasound signs (index tests) for detecting adnexal torsion, using surgical findings as the reference standard. The search for studies was performed in PubMed/MEDLINE, CINAHL, Scopus, The Cochrane Library, ClinicalTrials.gov and Web of Science databases. The Quality Assessment of Diagnostic Accuracy Studies‐2 (QUADAS‐2) tool was used to evaluate the quality of the studies. Pooled sensitivity, specificity, and positive and negative likelihood ratios were calculated separately, and the post‐test probability of adnexal torsion following a positive or negative test was also determined. Results: The search identified 1267 citations after excluding duplicates. Eighteen studies were ultimately included in the qualitative and quantitative syntheses. Eight studies (809 patients) analyzed the presence of ovarian edema, eight studies (1044 patients) analyzed the presence of an adnexal mass, 14 studies (1742 patients) analyzed ovarian Doppler flow, six studies (545 patients) analyzed the whirlpool sign and seven studies (981 patients) analyzed the presence of pelvic fluid as ultrasound signs of adnexal torsion. Overall, the quality of most studies was considered to be moderate or good. However, there was a high risk of bias in the patient‐selection and index‐text domains (with the exception of the whirlpool sign) in a significant proportion of studies. Pooled sensitivity, specificity, and positive and negative likelihood ratios of each ultrasound sign were 58%, 86%, 4.0 and 0.49 for ovarian edema, 69%, 46%, 1.3 and 0.67 for adnexal mass, 65%, 91%, 7.6 and 0.38 for the whirlpool sign, 53%, 95%, 11.0 and 0.49 for ovarian Doppler findings and 55%, 69%, 1.7 and 0.66 for pelvic fluid. Heterogeneity was high for all analyses. Conclusions: The presence of an adnexal mass or pelvic fluid have poor diagnostic accuracy as ultrasound signs of adnexal torsion, while the presence of ovarian edema, the whirlpool sign and decreased or absent ovarian Doppler flow have good specificity but moderate sensitivity for detecting adnexal torsion. © 2022 The Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of International Society of Ultrasound in Obstetrics and Gynecology. Abstract : A video abstract of this article is available online here .